Politique visant à prévenir et à combattre les violences à caractère sexuel (Annexe E) - École nationale de l'humour (2021)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer; Sophie-Anne

Why #MeToo Hasn’t Transformed the Stand-Up Scene - Baum, Gary (The Hollywood Reporter, 2021)
Female comics say that the empowerment movement has been met with pushback, retaliation and mockery from male counterparts: “If you’re a woman who’s been harassed, if you just talk about what happened, people perceive you as being some ‘cancel culture’ advocate.”
Keywords: Sophie-Anne

Indian Women in Comedy: : An Inquiry into the Perpetuation of Rape Culture on Social Media - Sharma, Mridula (Sanglap: Journal of Literary and Cultural Inquiry, 2021)
‘Postfeminist’ society has created the impression that contemporary discourses on gender representation, particularly in digital media platforms, are pointless. This misconception is coupled with online aggression by men’s rights activists who position feminist debates as sources of male oppression. However, media practices and consumption processes continue to maintain the supremacy of the male gender identity, which strengthens the process of transforming social media into a component of the “manosphere.” The failure of the fourth wave of feminism in utilising the Internet for mobilising activism for the ontological equality of all genders has succeeded by increasing gender-based violence against women. Indian women in comedy negotiate with these systemic inequalities while navigating male dominance in the comedy industry. The paper is an attempt to examine the structures of gender inequality and bias that affect the participation and advancement of women in the comedy circuit. Its focus remains on the formulation of a rape culture on social media and its subsequent consequences in the larger social context of the development of a patriarchal culture.
Keywords: Digital Abuse; Sophie-Anne

Portrait de la pratique de l'improvisation théâtrale en milieu scolaire et plan d'action pour son optimisation - Garneau, Jocelyn (L'escabeau, 2021)
Keywords: Bibliographie; Nettoyer; Sophie-Anne